(untitled) (The Review of Diabetic Studies, 2025)
Introduction: The program of the High-quality, safe, and integrated patient care is a systemic transformation of Saudi Arabia required by its Vision 2030, spearheaded by the Healthcare Sector Transformation Program. The Saudi Patient Safety Center (SPSC) and the Saudi Commission for Health Specialties (SCFHS) have developed explicit strategic mandates and competency frameworks, and as such the nurse workforce has been formally identified as a key to the national quality and safety (QPS) targets. . Study Objective: Main objective of study will be a systematic review and a systematic synthesis of current evidence of nursing involvement in Healthcare initiatives outlined in Saudi Arabia’s Vision 2030. Methodology: The systematic review approach was utilized to combine the data on national regulatory documents (SCFHS Scope of Practice ) and SPSC policies as well as the results of the empirical research published in 2013-2023. The review was conducted around the thematic areas like the occurrence of EBP barriers, professional autonomy, hierarchical structure, resource sufficiency, and high-risk activity outcomes such as medication safety and infection control. Conclusion: The role played by nurses is established as essential to the success of QPS, and there is evidence that nurses have effectively headed quality improvement initiatives. Nonetheless, the review ends with the conclusion that there is an important implementation gap between the high-level policy on the one hand and the reality of practice on the other hand, and that such gap is caused mainly by the structural and cultural barriers.